Factores predictivos de ingreso a unidad de cuidados intensivos en pacientes con COVID-19: un estudio de casos y controles - Cabral da Silva, Palena; da Silva Diniz, Alcides; Almeida de Noronha, Gisele; Lucia Diniz Araujo, Maria; Coelho Cabral, Poliana (Nutrición Clínica y Dietética Hospitalaria, 2021)
Objective: The aim of the present study was to evaluate potential predictive factors for the aggravation of COVID-19 in patients hospitalized at a reference hospital in northeastern Brazil. Methods: A non-paired case-control study was conducted with 235 patients hospitalized at a reference hospital in northeastern Brazil between March and April 2020. The case group was composed of individuals who required hospitalization in the ICU. The control group was composed of patients hospitalized due to COVID-19 who did not meet the criteria established in the institutional protocol for classification as “severe case of the disease” and therefore did not require intensive care. Results: The case group was composed of 84 patients with a median age of 45 years (P25-P75: 36-59); 63.1% were men; 56.0% were less than 60 years of age; 76.2% had excess weight; 14.3% had a previous heart disease; 46.4% had hypertension; 11.9% had lung disease; and 67.1% took continuous-use medications. The median stay of severe cases in the ICU was positively correlated with weight and BMI only among female patients less than 60 years of age. Conclusion: The logistic regression analysis revealed that age older than 60 years and a compromised cardiovascular system were independent predictive factors for the severity of COVID-19.